2008
DOI: 10.1186/gb-2008-9-5-r85
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals new insight into appressorium formation and function in the rice blast fungus Magnaporthe oryzae

Abstract: (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. Magnaporthe oryzae appressonium formulation

Analysis of genome-wide gene-expression changes during spore germination and appressorium formation in Magnaporthe oryzae revealed that protein degradation and amino-acid metabolism are essential for appressorium formation and subsequent infection.

Abstract Background: Rice blast dise…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
187
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(195 citation statements)
references
References 133 publications
(132 reference statements)
8
187
0
Order By: Relevance
“…Cerulenin is previously known to be a potent inhibitor of enzymes involved in fatty acid synthesis in a range of microorganisms (Omura, 1976). This group of enzymes is responsible for the production of lipids, which are vital components of cell plasma membrane (Campbell & Cronan, 2001;Oh et al, 2008). The damage caused by cerulenin to plasma membrane could be detected indirectly by staining the fungus cell wall structures using Calcofluor White reagent under fluorescent optical microscopy.…”
Section: Effect Of Cerulenin-containing Crude Extract Of S Oryzae Onmentioning
confidence: 99%
“…Cerulenin is previously known to be a potent inhibitor of enzymes involved in fatty acid synthesis in a range of microorganisms (Omura, 1976). This group of enzymes is responsible for the production of lipids, which are vital components of cell plasma membrane (Campbell & Cronan, 2001;Oh et al, 2008). The damage caused by cerulenin to plasma membrane could be detected indirectly by staining the fungus cell wall structures using Calcofluor White reagent under fluorescent optical microscopy.…”
Section: Effect Of Cerulenin-containing Crude Extract Of S Oryzae Onmentioning
confidence: 99%
“…DGE method uses data of relative tag frequencies to show gene expression differences [13]. Transcriptomic analysis has also been used to study pathogenicity-related genes [5]. Yeonyee Oh et al [5] reported the first comprehensive genome-wide transcript profile and the functional analysis of infection structure formation of Magnaporthe oryzae.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic analysis has also been used to study pathogenicity-related genes [5]. Yeonyee Oh et al [5] reported the first comprehensive genome-wide transcript profile and the functional analysis of infection structure formation of Magnaporthe oryzae. Gene knockout and complementary strategies have also been used to study the function of pathogenicity-related genes [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations